A resilience analysis on energy system: a preliminary case study for solar-assisted CCS. (December 2017) - Wang, Junyao; Sun, Taiwei; Deng, Shuai; Li, Kaixiang; Zhao, Jun; Gao, Liuhua; Wang, Yongzhen
Abstract: The concept of "resilience", which emerged in recent years, not only means an adaptive capacity to respond to disruptive challenge in a small scale of time, but also means a sustainable capacity to ecological remediation in a whole life cycle scale. Considering energy system is playing a significant role on the interaction process between nature environment and human society, the concept of "resilience" can definitely be drawn to the energy system as a measurement to evaluate the trade-off performance of available energy technologies embodied in various energy systems. Nonetheless, there is no existing approach to assess the resilience property of any energy system quantitatively and comprehensively. This study proposed a preliminary resilience analysis framework for energy systems. A case study is carried out for the emerging solar-assisted post carbon capture and storage process taking into account the criteria of life cycle GHG reduction potentials, primary energy consumptions (PED) as well as life cycle cost (LCC). Life cycle assessment (LCA), LCC analysis and grey relational analysis (GRA) methods are applied for integration assessment. Results show that applying solar energy for high-pressure feed-water heating performs best in terms of life cycle GHG mitigation as well as multi-criteria grey relational grade at 73.1% and 0.72 respectively.